Integrating E-Leanrning and Digital Assessment in Indonesian Maritime Vocational Education: Enhancing Work Readiness - Toko, Gigih Prastyan; Cahyadi, Tri; Robbany, Inayatur; Ridwan, Mohamad (Meteor STIP Marunda, 2025)
This qualitative study investigates the integration of E-learning and Digital Assessment at STIP Jakarta and its impact on the work readiness of Diploma-IV cadets, aligned with international STCW competency standards. Through in-depth interviews and focus group discussions with 70 final-year cadets, the research reveals a dualistic outcome: while digital tools are highly effective in delivering theoretical knowledge and developing simulator-based operational skills, they exhibit significant limitations in fostering hands-on practical abilities and essential psychosocial competencies such as leadership and mental resilience. The findings identify a critical "digital-practical divide," where cadets report high digital confidence alongside underlying anxiety about real-world application. The study concludes that a balanced, hybrid pedagogical model is essential, leveraging technology not as a replacement but as a complement to traditional practical training. This approach is vital for Indonesia’s maritime sector to develop truly work-ready graduates who are both technologically proficient and psychologically prepared.